COOLIST (Cooling for Ischemic Stroke Trial): A Multicenter, Open, Randomized, Phase II, Clinical Trial. Issue 1 (January 2017) - Geurts, Marjolein; Petersson, Jesper; Brizzi, Marco; Olsson-Hau, Stefan; Luijckx, Gert-Jan; Algra, Ale; Dippel, Diederik W.J.; Kappelle, L. Jaap; van der Worp, H. Bart
Abstract : Background and Purpose—: Animal studies suggest that cooling improves outcome after ischemic stroke. We assessed the feasibility and safety of surface cooling to different target temperatures in awake patients with acute ischemic stroke. Methods—: A multicenter, randomized, open, phase II, clinical trial, comparing standard treatment with surface cooling to 34.0°C, 34.5°C, or 35.0°C in awake patients with acute ischemic stroke and an National Institutes of Health Stroke Scale score of ≥6, initiated within 4.5 hours after symptom onset and maintained for 24 hours. The primary outcome was feasibility, defined as the proportion of patients who had successfully completed the assigned treatment. Safety was a secondary outcome. Results—: Inclusion was terminated after 22 patients because of slow recruitment. Five patients were randomized to 34.0°C, 6 to 34.5°C, 5 to 35.0°C (cooling was initiated in 4), and 6 to standard care. No (0%), 1 (17%), and 3 (75%) patients, respectively, completed the assigned treatment ( P =0.03). No (0%), 2 (33%), and 4 (100%) patients reached the target temperature ( P =0.01). Pneumonia occurred in 8 cooled patients but not in controls (absolute risk increase, 53%; 95% confidence interval, 28–79%; P =0.002). Conclusions—: In awake patients with acute ischemic stroke, surface cooling is feasible to 35.0°C, but not to 34.5°C and 34.0°C. Cooling is associated with an increased risk of pneumonia. Clinical Trial Registration—: URL:http://www.trialregister.nl . Unique identifier: NTR2616. Abstract : Supplemental Digital Content is available in the text.